Nutritional practices of public elementary school pupils and teachers in Pateros - Mora, Sophia S.; Moreno, Keena S.; Nabong, Earl Bradley A.; Orilla, Kharissa Anne P.; Poltic, Faith Nester .; Reyes, Jazzel Joy G.; Olea, Kert Howard S. (Manila College of Nursing University of the Philippines Manila, 2018)
There is a growing public health concern of increasing rates of childhood obesity and this is 30% higher in developing countries like the Philippines (PHRD,2015). Eating habits are founded on adequate knowledge and positive nutritional attitude. Upon entry into school, the nutritional practices of children become highly influenced by environmental factors including their teachers (Williams and Mummery, 2015). However, little is known about pupils’ practices and the role of teachers in addressing gaps in their nutritional knowledge, attitudes, and practices. The study aims to determine the nutritional practices of school children and the factors that may influence this. Specifically, the objectives were (1) to describe the nutritional practices of public elementary school pupils and teachers; (2) to compare the nutritional knowledge, attitude, and practices with teachers; and (3) to determine the factors affecting nutritional practices of pupils.

The study used a descriptive correlational design and was conducted in all seven public elementary schools in the municipality of Pateros. For pupils, proportional quota sampling was used. All public elementary school teachers were invited to participate. A total of 592 pupils and 114 teachers were included in the study. A self-administered tool was adopted from Gamaro (2012) was used for both pupils and teachers.

Results showed that pupils eat their meals regularly and they always had breakfast, lunch, and dinner. Regularity of meals serves as an important part of their nutrition practice since this affects the amount of nutrient intake their body receives for growth and development. It was also found out that the pupils often had morning, afternoon, and sometimes, evening snacks. Pupils had moderate nutritional knowledge wherein majority of the incorrect answers were observed among questions relating to the composition and functions of certain foods. Nutritional knowledge of pupils was found to have a weak negative relationship with nutrition practice of skipping of meals wherein the higher the nutrition knowledge, the less likely it is to skip meals. Teachers had high nutritional knowledge and common errors were on misconceptions regarding nutrition. They had a significantly higher score on knowledge compared to pupils. Teachers as adults and having higher level of education have higher nutritional knowledge. On nutritional attitude, both pupils and teachers have a moderate positive attitude towards nutrition. For both pupils and teachers, nutritional attitude was found to have a weak positive correlation with healthy food intake. Positive attitude towards nutrition plays an important role in improving the nutrition practices among school children. Based on these results several recommendations were made such as including parents and school environment as other factors that may affect pupil's nutritional practices.
Research (In partial fulfillment of the requirements of the course N121.1: Intensive Nursing Experience, Hospital-based) -- University of the Philippines Manila, June 2018.
Keywords: Intensive nursing experienced -- Hospital-based.